Current evidence on the effect of dietary polyphenols intake on chronic diseases - Costa, Chiara; Tsatsakis, Aristidis; Mamoulakis, Charalampos; Teodoro, Michele; Briguglio, Giusi; Caruso, Emanuela; Tsoukalas, Dimitris; Margina, Denisa; Dardiotis, Efthimios; Kouretas, Demetrios; Fenga, Concettina (Food and chemical toxicology, 2017)
Polyphenols are secondary metabolites of plants. They comprise several antioxidant compounds and they are generally considered to be involved in the defense against human chronic diseases. During the last years, there has been growing scientific interest in their potential health benefits. In this comprehensive review, we focus on the current evidence defining the position of their dietary intake in the prevention/treatment of human chronic diseases, including prostate cancer and other types of cancer, cardiovascular diseases, diabetes mellitus and neurodegenerative diseases such as Alzheimer's and Parkinson's disease; we also discuss their ability to modulate multiple signalling transduction pathways involved in the pathophysiology of these diseases. Despite the fact that data regarding the biological functions of polyphenols can be considered exhaustive, evidence is still inadequate to support clear beneficial effects on human chronic diseases. Currently, most data suggest that a combination of phytochemicals rather than any single polyphenol is responsible for health benefit. More studies investigating the role of polyphenols in the prevention of chronic human diseases are needed, especially for evaluating factors such as gender, age, genotype, metabolism and bioavailability. •Regular dietary intake of polyphenols (PF) may reduce the risk of chronic diseases.•PF may protect cardiovascular system, glucose homeostasis, brain and from cancer.•PF could be a novel pharmacological approach for chronic diseases management.•Response after consumption of plant food bioactive compounds presents inter-individual variability.•Evidence is not still adequate to support clear effects on human health.